Borealin/CDCA8 deficiency alters thyroid development and results in papillary tumor-like structures - Didier-Mathon, Hortense; Stoupa, Athanasia; Kariyawasam, Dulanjalee; Yde, Sonny; Cochant-Priollet, Beatrix; Groussin, Lionel; Sébag, Frédéric; Cagnard, Nicolas; Nitschke, Patrick; Luton, Dominique; Polak, Michel; Carré, Aurore (Frontiers in Endocrinology, 2023)
Background BOREALIN/CDCA8 mutations are associated with congenital hypothyroidism and thyroid dysgenesis. Borealin is involved in mitosis as part of the Chromosomal Passenger Complex. Although BOREALIN mutations decrease thyrocyte adhesion and migration, little is known about the specific role of Borealin in the thyroid. Methods We characterized thyroid development and function in Borealin-deficient (Borealin+/−) mice using histology, transcriptomic analysis, and quantitative PCR. Results Thyroid development was impaired with a hyperplastic anlage on embryonic day E9.5 followed by thyroid hypoplasia from E11.5 onward. Adult Borealin+/− mice exhibited euthyroid goiter and defect in thyroid hormone synthesis. Borealin+/− aged mice had disorganized follicles and papillary-like structures in thyroids due to ERK pathway activation and a strong increase of Braf-like genes described by The Cancer Genome Atlas (TCGA) network of papillary thyroid carcinoma. Moreover, Borealin+/− thyroids exhibited structural and transcriptomic similarities with papillary thyroid carcinoma tissue from a human patient harboring a BOREALIN mutation, suggesting a role in thyroid tumor susceptibility. Conclusion These findings demonstrate Borealin involvement in critical steps of thyroid structural development and function throughout life. They support a role for Borealin in thyroid dysgenesis with congenital hypothyroidism. Close monitoring for thyroid cancer seems warranted in patients carrying BOREALIN mutations.